2014
DOI: 10.1103/physrevc.90.065803
|View full text |Cite
|
Sign up to set email alerts
|

Beyond nuclear “pasta” : Phase transitions and neutrino opacity of new “pasta” phases

Abstract: In this work, we focus on different length scales within the dynamics of nucleons in conditions according to the neutron star crust, with a semiclassical molecular dynamics model, studying isospin symmetric matter at subsaturation densities. While varying the temperature, we find that a solidliquid phase transition exists, that can be also characterized with a morphology transition. For higher temperatures, above this phase transition, we study the neutrino opacity, and find that in the liquid phase, the scatt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 39 publications
6
42
0
Order By: Relevance
“…At large proton fractions and low enough temperatures the nucleons in the simulation undergo a phase transition to a solid microphase. These dynamics were recently observed in MD simulations of pasta by Alcain et al [10], who found that the nucleons undergo a solid-liquid phase transition at low densities near T = 0.5 MeV. Since at the temperatures and densities simulated in this work nucleons are not expected to form a lattice, even at zero temperature, this …”
Section: A Expansion Ratesupporting
confidence: 79%
See 3 more Smart Citations
“…At large proton fractions and low enough temperatures the nucleons in the simulation undergo a phase transition to a solid microphase. These dynamics were recently observed in MD simulations of pasta by Alcain et al [10], who found that the nucleons undergo a solid-liquid phase transition at low densities near T = 0.5 MeV. Since at the temperatures and densities simulated in this work nucleons are not expected to form a lattice, even at zero temperature, this …”
Section: A Expansion Ratesupporting
confidence: 79%
“…Current computational limits restrict MD simulation expansion rates in Eq. (3b) to 10 12 or more times faster. This corresponds to a maximum of about 10 10 MD time steps.…”
Section: A Expansion Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Although several authors [8,[37][38][39] have studied transport properties of the crust, very few studies employed dynamical approach. At first, Horowitz et al [3,4] and recently Alcain et al [40] studied neutrino-pasta scattering adopting classical molecular dynamics. Horowitz et al [6], Horowitz & Berry [19] also estimated the values of the shear viscosity and thermal conductivity of the pasta phase but only for a few densities and a single temperature and proton fraction.…”
Section: Introductionmentioning
confidence: 99%